Molecular diagnosis of Huntington disease in Portugal: implications for genetic counselling and clinical practice - Costa, MC (2003)
Huntington disease (HD) is a neurodegenerative, autosomal dominant disorder of late-onset, caused by the expansion of a CAG repeat in the coding region of the gene. Ours is the reference laboratory for genetic testing in HD, in Portugal, since 1998; 90.1% of all 158 families known were identified for the first time, including patients with unusual presentation or without family history. A total of 338 genetic tests were performed: 234 for diagnosis, 96 for presymptomatic and four for prenatal testing (four were done for family studies). Most referring physicians were neurologists (90.6%); 82.8% of all clinical diagnosis were confirmed, while 83.1% of those sent for exclusion were in fact excluded. In presymptomatic testing, an excess of female subjects (59.4%) was again verified; 37.5% of the consultands were found to be carriers. None of the foetuses, in four prenatal tests, were mutation carriers. One juvenile case was inherited from her mother. Our patient population is very similar to others described so far, namely in terms of mean age at onset and (CAG)(n) distribution, except perhaps for a higher frequency of large normal (class 2) alleles (3.7%). We also identify cases posing particular problems for genetic counselling, such as, 'homozygosity' that can pose a serious ethical dilemma, carriers of large normal alleles, and 'homoallelism' for a normal gene, which will demand further procedures and may delay results in presymptomatic and prenatal testing.